2021
DOI: 10.1007/s12035-021-02601-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model

Abstract: Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…However, the discrepancies between the induction protocols and the absence of common evaluation criteria could impact the differentiation capacity of the stem cell pool, which requires special attention. ASCs' isolation and characterization protocols were previously reported from our group for horse [23], dog [24], and rat cells [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the discrepancies between the induction protocols and the absence of common evaluation criteria could impact the differentiation capacity of the stem cell pool, which requires special attention. ASCs' isolation and characterization protocols were previously reported from our group for horse [23], dog [24], and rat cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…The list of primary and secondary antibodies used in the current study to detect ASC markers, their target species, and their cross reactivity between species are listed in (Table S1). The protocol for ASCs' multipotency was previously described in detail by our group in horse [23], dog [24], and rat cells [25]. Cells of passages P1-P4 from all animal groups and humans were expanded and then used for all experimental procedures.…”
Section: Isolation Of Ascsmentioning
confidence: 99%
“…Moreover, neuronal Ca 2+ responses upon application of excitatory neurotransmitters (glutamate, substance P) were modulated by LPS stimulation. Based on these results, we showed that this in vitro tool can further be applied to study pathophysiological mechanisms including LPS tolerance [34], as well as immunomodulatory capacities of novel treatments such as co-cultivation with adipose tissue-derived medicinal signaling cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that neuro-glial primary cell cultures of the rat SDH are a valuable tool to study effects of inflammatory stimulation on neuronal responses, production of inflammatory mediators, and activation of inflammatory transcription factors in vitro [26]. Thus, this approach is also useful to study putative anti-inflammatory or anti-nociceptive capacities of novel therapeutic interventions, such as cell-based therapy [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, CD11a/18, CD45, CD44, CD90, CD105, and MHCII were applied as markers. The FACS analysis was performed as described before by Leisengang et al (26). We also tested the proportion of live cells by, staining with 7amino-actinomycin D (7-AAD, Becton Dickinson, Heidelberg, Germany).…”
Section: Facs-analysismentioning
confidence: 99%